Isolation and identification of Aspergillus niger degrading thermoplastic starch from compost soil: article - Mohd Fuaad, Ain Nadhirah; Mohd Sauid, Suhaila (2017)
In this research study, TPS are serves as the bio plastic that need to be degrade by the microbial action. The study was focused on the degradation by Aspergillus sp which are fungi species. The source of the fungi was obtained from the isolation of the fungi sp from the compost soil. Primarily, the microbes were identified and isolated from dilute soil compost. The microbes were streaked and let it grow on the selective media which are PDA agar to identify it as a fungi species. At once, TPS were prepared and let the fungi degrade it. The optimal temperature for the incubation process was 37° C and the duration of the study was two weeks. The identification of fungi sp by morphological characteristics identified that the fungi sp was Aspergillus sp Starch hydrolysis also were done to indicate the presence of the amylase enzyme that were hydrolyze the starch. The presence of amylase will create a clear halos zone surrounding colonies which indicate their ability to digest starch. Next, the biodegradation of TPS film was study based on weight loss of the TPS film. The TPS film showed a decreasing in weight value during the observation. It can be concluded that, Aspergillus sp from compost soil are one of the microorganism that are responsible for the thermal plastic degradation.